“Creative Translation” as Political Defamation: Hanuš Kuffner’s Great Czech State Utopia and its Propagandistic Instrumentalization against Czechoslovakia - Blahak, Boris (Studia Philologica, 2023)
In his political memorandum Náš stát a světový mír, published in Prague in 1918, the Czech military historian and national extremist Hanuš Kuffner called for a fundamental political reordering of the world that included the territorial curtailment and permanent military control of Germany and the creation of a defensible Great Czech state to which large parts of Germany, Austria and Hungary would be annexed. Although published in only a small number of copies, the pamphlet quickly became the most cited Czech work in the folkish German nationalist literature of the 1920s and 1930s, and was constantly referred to in order to ʻexpose’ the ʻreal aims’ of the Czechoslovak government towards Germany. The article reconstructs the facets of the political instrumentalization of the pamphlet in Sudeten and Reich German circles against Czechoslovakia. The focus is on its German-language basis: the translation Unser Staat und der Weltfrieden (Our State and World Peace), published in Warnsdorf/Bohemia in 1922. It will be shown that this was not a literal translation of the text, but a ʻdidacticised’ version intended for a German readership with no knowledge of Czech, which tended to intensify the already violence-laden pamphlet at crucial points. On the other hand, the ʻcreative’ handling of the map material that Kuffner included in his pamphlet by German nationalist authors is to be examined. Here, in the course of time, an increasingly clear identification of the state utopia of 1918 with the geopolitical reality of the 1930s became apparent in numerous reproductions.